Struktur dan Fungsi Hasehawaka Manu Kakae pada Masyarakat Tetun Fehan, Desa Forek Modok - Serafina Dahu (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2018)
In this research, the author wants to find our structure and function in Hasehawaka Manu Kakae in Tetun Fehan society in Forekmodok village. This research aims at describing structure and function in Hasehawaka Manu Kakae. Method used in this research was qualitative descriptive by using observation, interview with recording and note technique. The result shows that structure and function in Hasehawaka Manu Kakae consist of diction, line, couplet, voice that consists of rhyme, rhythm an other voice such as euphony and cacophony, and language style. Besides, function found in Hasehawaka Manu Kakae consists of social, educative and cultural functions.